Synthesis method of polymer solid electrolyte with alternately distributed lithium salts and ion conduction chain segments and preparation of film of polymer solid electrolyte
By using the synthesis method of polymer solid electrolytes (ASPEs) with alternately distributed lithium salts and conductive chain segments in lithium-ion batteries, the problems of lithium dendrites and capacity decay in lithium-ion batteries are solved, and higher battery safety is achieved and energy density.
Patent Information
- Application Number
- CN202311050182.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-21
- Publication Date
- 2025-02-21
AI Technical Summary
In existing lithium-ion batteries, side reactions are prone to occur when the liquid electrolyte comes into contact with the lithium metal negative electrode material, resulting in the generation of lithium dendrites and capacity attenuation, affecting the safety and energy density of the battery.
The synthesis method of polymer solid electrolytes (ASPEs) with alternating distribution of lithium salts and conductive segments is adopted, and the lithium salt monomer of 4-(trifluoromethoxy)-styrene bissulfonimide is alternately copolymerized with maleic anhydride. , combine amino octaglycol monomethyl ether and bisamino oligomeric PEG to form a uniformly distributed electrolyte structure.
The uniform distribution of Li+ source and ionic conductive chain segments is achieved, the ionic conductivity of the electrolyte is improved, the safety and energy density of the battery are enhanced, and the generation of lithium dendrites is avoided.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The invention relates to a method for synthesizing a solid polymer electrolyte, in particular to a method for synthesizing a polymer solid electrolyte (ASPEs) in which lithium salts and ion-conducting segments are alternately distributed and a film preparation thereof, belonging to the field of energy technology. Background Art
[0002] Environmental pollution, global warming and fossil energy reduction have become one of the inevitable problems for mankind in the 21st century. Scientists have been committed to the development and application of new energy. In addition, lithium-ion batteries have become an important new energy source since their commercialization in 1991 and are widely used in various electronic devices. However, with the continuous improvement of people's living standards, the most advanced lithium-ion batteries cannot even meet practical needs due to their limited energy density, especially in the field of electric vehicles. Lithium metal batteries (LMBs) are considered to be the next generation of rechargeable batteries because the theoretical energy density of lithium metal is high (3860mA hg -1 ). However, when lithium metal contacts with conventional liquid electrolytes during charging in LMBs as negative electrode materials, some side reactions inevitably occur, and then irregular metallic lithium deposits are generated, leading to the generation of lithium dendrites and rapid capacity decay. Unfortunately, lithium dendrite growth is one of the fundamental issues affecting the safety and stability of lithium batteries. Solid polymer electrolytes (SPEs) are an excellent strategy to address the above issues, thereby improving safety and energy density. In fact, low ionic conductivity and low lithium ion transference number (LTN) greatly limit their practical applications. Although many alternative polymer hosts have been explored over the years, most of the research on solid electrolytes is still based on polyether-based materials, especially polyethylene oxide. The high crystallinity of high molecular weight PEO and the random distribution of lithium ion conductive segments based on PEO are known to be the main reasons for the low ionic conductivity. In addition, the lithium salts in conventional SPEs are dissolved in the polymer matrix (usually high molecular weight PEO), in which both lithium ions and their corresponding anions can move. Li+ is usually less mobile than anions, resulting in polarization, lithium dendrite growth, concentration gradients between electrodes, and even eventually battery failure. In addition, covalently attaching anions to the polymer backbone is one of the most important methods to achieve single Li-ion conduction. In summary, the structural design of SPEs that enables uniform distribution of Li+ sources and ion-conducting segments, reducing the crystallinity of the system, and designing the polymer backbone to restrict anion mobility to result in single Li-ion conduction are important solutions to achieve superior performance of solid polymer electrolytes. Summary of the invention
[0003] The purpose of the present invention is to provide a method for synthesizing polymer solid electrolytes (ASPEs) with alternating distribution of lithium salts and conductive segments and the preparation of their films. The unique structure of alternating distribution of lithium salts and conductive segments achieves uniform distribution of Li+ sources and ion conductive segments at the microscopic level, which is beneficial to improving the ion conductivity of the electrolyte. The present invention adopts the following technical solutions:
[0004] The present invention relates to a method for synthesizing a polymer solid electrolyte in which lithium salts and conductive segments are alternately distributed, and the characteristic steps are as follows:
[0005] 1) Preparation of 4-(trifluoromethoxy)-phenylene bissulfonyl imide lithium salt monomer: 4-(trifluoromethoxy)-benzenesulfonamide, triethylamine and 4-dimethylaminopyridine are mixed in a three-necked flask, and then acetonitrile is added to dissolve and evenly disperse the mixture, and then the mixture is placed in an ice bath at 0°C. P-styrenesulfonyl chloride having an equal mass to 4-(trifluoromethoxy)-benzenesulfonamide is evenly dispersed in acetonitrile and added dropwise to the acetonitrile solution of benzenesulfonamide. After the addition is completed, the mixture is allowed to stand at 0°C for 0.5 to 1 hour, and then the mixture is heated to room temperature of 25 to 30°C for reaction to obtain phenylene bissulfonyl imide. Then, 4-(trifluoromethoxy)-benzenesulfonamide and lithium hydroxide in an equal molar ratio are placed in distilled water and stirred until a transparent solution is obtained. The distilled water is dried using a rotary evaporator to obtain a 4-(trifluoromethoxy)-benzenesulfonamide lithium salt monomer.
[0006] 2) Preparation of alternating copolymer lithium salt: 4-(trifluoromethoxy)-phenylvinylbissulfonyl imide lithium salt monomer and maleic anhydride are uniformly dispersed in dimethyl sulfoxide solvent, azobisisobutyronitrile as a thermal initiator is added, and after excluding oxygen, the temperature is raised to above 80°C for polymerization reaction. When copolymerizing, a slight excess of maleic anhydride is selected so that the copolymerization of the phenylvinyl derivative and maleic anhydride tends to be alternating polymerization.
[0007] 3) Preparation method of polymer solid electrolytes (ASPEs) with alternating distribution of lithium salts and conductive chains:
[0008] Alternating polymer lithium salt, aminooctaethylene glycol monomethyl ether (NH2-(CH2CH2O)-), and diamino oligomeric PEG (NH2-PEG-NH2, Mw=2000) were added to a three-necked flask and reacted for 8-14 hours in an argon environment to obtain a polymer solid electrolyte with alternating distribution of lithium salt and conductive chain segments.
[0009] 4) Preparation method of thin film of polymer solid electrolyte (ASPEs) with alternating distribution of lithium salt and conductive chain segments:
[0010] The synthesized electrolyte material was dissolved in dimethyl sulfoxide, heated and uniformly dispersed for 6-12 hours, and the uniform solution was poured into a PTFE petri dish and placed on a 70°C heating table for 24 hours to evaporate the solvent. The PTFE petri dish was then placed in an 80°C vacuum oven and heated for 10 hours to remove the residual solvent, thereby obtaining the final electrolyte film.
[0011] Preferably, in step 1), the molar ratio of triethylamine to benzenesulfonamide is (1-5):1, and the molar ratio of 4-dimethylaminopyridine to benzenesulfonamide is (1-3):1;
[0012] Preferably, the reaction temperature of step 2) is 75-80°C.
[0013] Preferably, in step 2), the molar ratio of 4-(trifluoromethoxy)-phenylene bissulfonylimide lithium salt monomer to maleic anhydride is 1:(1-1.25), and the preferred ratio is 1:(1.05-1.2).
[0014] Preferably, in step 3), the ratio of the amount of amino octaethylene glycol monomethyl ether (NH2-(CH2CH2O)-) to the amount of diamino oligomeric PEG (NH2-PEG-NH2, Mw=2000) is (2-4):1.
[0015] The present invention uses maleic anhydride as a reaction site to graft lithium ion conductive segments onto the polymer main chain. The structure of the alternating copolymer allows the grafted ion conductive segments and the lithium ion source to be alternately and evenly distributed. At the same time, the introduction of diamino oligomeric PEG allows the system to form a cross-linked structure, providing film-forming properties and avoiding the use of high molecular weight PEO (high molecular weight PEO usually has very high crystallinity). BRIEF DESCRIPTION OF THE DRAWINGS
[0016] Figure 1 The structural formula of a polymer solid electrolyte with alternating distribution of lithium salt and conductive chain segments
[0017] Figure 2 is the hydrogen nuclear magnetic resonance spectrum of the 4-(trifluoromethoxy)-phenylene bissulfonyl imide lithium salt monomer of the present invention;
[0018] Figure 3 is the carbon nuclear magnetic resonance spectrum of the alternating copolymer lithium salt obtained in the present invention;
[0019] Figure 4 The hydrogen nuclear magnetic resonance spectrum of the polymer solid electrolyte (ASPEs) with alternating distribution of lithium salt and conductive chain segments obtained by the present invention;
[0020] Figure 5 Schematic diagram of a thin film of a polymer solid electrolyte with alternating distribution of lithium salts and conductive chains.
[0021] Figure 6This is the AC impedance diagram of the polymer solid electrolyte with alternating distribution of lithium salt and conductive chain segments at 30℃-80℃. DETAILED DESCRIPTION
[0022] Three embodiments of the present invention are provided below to further illustrate the present invention, but not to limit the scope of the present invention.
[0023] Example 1
[0024] 1) Preparation of 4-(trifluoromethoxy)-phenylene bissulfonyl imide lithium salt monomer: 1.789 g of 4-(trifluoromethoxy)-benzenesulfonamide, 3.5 ml of triethylamine and 0.907 g of 4-dimethylaminopyridine were mixed in a flask, and then 20 ml of acetonitrile was added to dissolve and evenly disperse the mixture, and then placed in an ice bath at 0° C. 1.5 g of p-phenylenesulfonyl chloride was evenly dispersed in acetonitrile and added dropwise to the acetonitrile solution of benzenesulfonamide. After the addition was completed, the mixture was allowed to stand at 0° C. for 0.5 hour, and then the mixture was heated to room temperature of 25° C. for reaction to obtain phenylene bissulfonyl imide. The prepared 4-(trifluoromethoxy)-benzenesulfonamide and lithium hydroxide were placed in distilled water and stirred until a transparent solution was obtained. The distilled water was dried using a rotary evaporator to obtain a 4-(trifluoromethoxy)-benzenesulfonamide lithium salt monomer.
[0025] 2) Preparation of alternating copolymer lithium salt: 1 g of 4-(trifluoromethoxy)-phenylvinylbissulfonyl imide lithium salt monomer and 0.2 g of maleic anhydride are uniformly dispersed in dimethyl sulfoxide solvent, 0.035 g of azobisisobutyronitrile as a thermal initiator is added, and after excluding oxygen, the temperature is raised to above 80°C for polymerization reaction. When performing the copolymerization, a slight excess of maleic anhydride is selected so that the copolymerization of the phenylvinyl derivative and maleic anhydride tends to be alternating polymerization.
[0026] 3) Preparation method of polymer solid electrolytes (ASPEs) with alternating distribution of lithium salts and conductive chains:
[0027] 2.525g of alternating polymer lithium salt, 1.532g of aminooctaethylene glycol monomethyl ether (NH2-(CH2CH2O)-), and 2g of diamino oligomeric PEG (NH2-PEG-NH2, Mw=2000) were added to a three-necked flask and reacted under argon environment for 8-14h to obtain a polymer solid electrolyte with alternating distribution of lithium salt and conductive chain segments.
[0028] 4) Preparation method of thin film of polymer solid electrolyte (ASPEs) with alternating distribution of lithium salt and conductive chain segments:
[0029] The synthesized electrolyte material was dissolved in dimethyl sulfoxide, heated and uniformly dispersed for 7 hours, and the uniform solution was poured into a PTFE petri dish and placed on a 70°C heating table for 24 hours to evaporate the solvent. The PTFE petri dish was then placed in an 80°C vacuum oven and heated for 10 hours to completely evaporate the solvent, thereby obtaining the final electrolyte film.
[0030] Example 2
[0031] 1) Preparation of 4-(trifluoromethoxy)-phenylene bissulfonyl imide lithium salt monomer: 1.789 g of 4-(trifluoromethoxy)-benzenesulfonamide, 3.5 ml of triethylamine and 0.907 g of 4-dimethylaminopyridine were mixed in a flask, and then 20 ml of acetonitrile was added to dissolve and evenly disperse the mixture, and then placed in an ice bath at 0° C. 1.5 g of p-phenylenesulfonyl chloride was evenly dispersed in acetonitrile and added dropwise to the acetonitrile solution of benzenesulfonamide. After the addition was completed, the mixture was allowed to stand at 0° C. for 0.5 hour, and then the mixture was heated to room temperature of 25° C. for reaction to obtain phenylene bissulfonyl imide. The prepared 4-(trifluoromethoxy)-benzenesulfonamide and lithium hydroxide were placed in distilled water and stirred until a transparent solution was obtained. The distilled water was dried using a rotary evaporator to obtain a 4-(trifluoromethoxy)-benzenesulfonamide lithium salt monomer.
[0032] 2) Preparation of alternating copolymer lithium salt: 1 g of 4-(trifluoromethoxy)-phenylvinylbissulfonyl imide lithium salt monomer and 0.2 g of maleic anhydride are uniformly dispersed in dimethyl sulfoxide solvent, 0.035 g of azobisisobutyronitrile as a thermal initiator is added, and after excluding oxygen, the temperature is raised to above 80°C for polymerization reaction. When performing the copolymerization, a slight excess of maleic anhydride is selected so that the copolymerization of the phenylvinyl derivative and maleic anhydride tends to be alternating polymerization.
[0033] 3) Preparation method of polymer solid electrolytes (ASPEs) with alternating distribution of lithium salts and conductive chains:
[0034] 2.273g of alternating polymer lithium salt, 1.149g of aminooctaethylene glycol monomethyl ether (NH2-(CH2CH2O)-), and 3g of diamino oligomeric PEG (NH2-PEG-NH2, Mw=2000) were added to a three-necked flask and reacted under argon environment for 8h to obtain a polymer solid electrolyte with alternating distribution of lithium salt and conductive chain segments.
[0035] 4) Preparation method of thin film of polymer solid electrolyte (ASPEs) with alternating distribution of lithium salt and conductive chain segments:
[0036] The synthesized electrolyte material was dissolved in dimethyl sulfoxide, heated and uniformly dispersed for 7 hours, and the uniform solution was poured into a PTFE petri dish and placed on a 70°C heating table for 24 hours to evaporate the solvent. The PTFE petri dish was then placed in an 80°C vacuum oven and heated for 10 hours to completely evaporate the solvent, thereby obtaining the final electrolyte film.
[0037] Example 3
[0038] 1) Preparation of 4-(trifluoromethoxy)-phenylene bissulfonyl imide lithium salt monomer: 1.789 g of 4-(trifluoromethoxy)-benzenesulfonamide, 3.5 ml of triethylamine and 0.907 g of 4-dimethylaminopyridine were mixed in a flask, and then 20 ml of acetonitrile was added to dissolve and evenly disperse the mixture, and then placed in an ice bath at 0° C. 1.5 g of p-phenylenesulfonyl chloride was evenly dispersed in acetonitrile and added dropwise to the acetonitrile solution of benzenesulfonamide. After the addition was completed, the mixture was allowed to stand at 0° C. for 0.5 hour, and then the mixture was heated to room temperature of 25° C. for reaction to obtain phenylene bissulfonyl imide. The prepared 4-(trifluoromethoxy)-benzenesulfonamide and lithium hydroxide were placed in distilled water and stirred until a transparent solution was obtained. The distilled water was dried using a rotary evaporator to obtain a 4-(trifluoromethoxy)-benzenesulfonamide lithium salt monomer.
[0039] 2) Preparation of alternating copolymer lithium salt: 1 g of 4-(trifluoromethoxy)-phenylvinylbissulfonyl imide lithium salt monomer and 0.2 g of maleic anhydride are uniformly dispersed in dimethyl sulfoxide solvent, 0.035 g of azobisisobutyronitrile as a thermal initiator is added, and after excluding oxygen, the temperature is raised to above 80°C for polymerization reaction. When performing the copolymerization, a slight excess of maleic anhydride is selected so that the copolymerization of the phenylvinyl derivative and maleic anhydride tends to be alternating polymerization.
[0040] 3) Preparation method of polymer solid electrolytes (ASPEs) with alternating distribution of lithium salts and conductive chains:
[0041] 3.03g of alternating polymer lithium salt, 1.915g of aminooctaethylene glycol monomethyl ether (NH2-(CH2CH2O)-), and 2g of diamino oligomeric PEG (NH2-PEG-NH2, Mw=2000) were added to a three-necked flask and reacted under argon environment for 10h to obtain a polymer solid electrolyte with alternating distribution of lithium salt and conductive chain segments.
[0042] 4) Preparation method of thin film of polymer solid electrolyte (ASPEs) with alternating distribution of lithium salt and conductive chain segments:
[0043] The synthesized electrolyte material was dissolved in dimethyl sulfoxide, heated and uniformly dispersed for 7 hours, and the uniform solution was poured into a PTFE petri dish and placed on a 70°C heating table for 24 hours to evaporate the solvent. The PTFE petri dish was then placed in an 80°C vacuum oven and heated for 10 hours to completely evaporate the solvent, thereby obtaining the final electrolyte film.
[0044] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A method for preparing a polymer solid electrolyte in which lithium salt and ion-conducting segments are alternately distributed, and the structural formula is as follows:
2. The method for preparing the polymer solid electrolyte with alternating distribution of lithium salt and conductive chain segments according to claim 1, characterized in that: Alternating polymer lithium salt, aminooctaethylene glycol monomethyl ether (NH2-(CH2CH2O)-), and diamino oligomeric PEG (NH2-PEG-NH2, Mw=2000) were added to a three-necked flask and reacted at 60°C for 8-14h under argon environment to obtain a polymer solid electrolyte with alternating distribution of lithium salt and ion conductive chain segments.
3. The method for preparing the alternating copolymer lithium salt according to claim 2, characterized in that: 4-(trifluoromethoxy)-phenylvinylbissulfonyl imide lithium salt monomer and maleic anhydride are uniformly dispersed in a solvent of dimethyl sulfoxide, a thermal initiator azobisisobutyronitrile is added, and after excluding oxygen, the temperature is raised to above 80°C for polymerization reaction. When copolymerization is carried out, a slight excess of maleic anhydride is selected so that the copolymerization of the phenylvinyl derivative and the maleic anhydride tends to be alternating polymerization. The molar ratio of the 4-(trifluoromethoxy)-phenylvinylbissulfonyl imide lithium salt monomer to the maleic anhydride is 1:(1-1.25), and the preferred ratio is 1:(1.05-1.2).
4. The method for preparing the 4-(trifluoromethoxy)-phenylene bissulfonyl imide lithium salt monomer according to claim 3, characterized in that: The 4-(trifluoromethoxy)-phenylene bissulfonyl imide lithium salt monomer is prepared by the following steps: 4-(trifluoromethoxy)-benzenesulfonamide, triethylamine and 4-dimethylaminopyridine are mixed in a flask, then acetonitrile is added to dissolve and evenly disperse the mixture, and then the mixture is placed in an ice bath at 0°C, wherein the molar ratio of triethylamine to benzenesulfonamide is (1-5):1, and the molar ratio of 4-dimethylaminopyridine to benzenesulfonamide is (1-3):1; and 4-(trifluoromethoxy)-benzenesulfonamide, benzenesulfonamide and the like are mixed. The mass of p-styrenesulfonyl chloride is uniformly dispersed in acetonitrile and added dropwise to the acetonitrile solution of benzenesulfonamide. After the addition is completed, the mixture is allowed to stand at 0°C for 0.5-1 hour, and then the mixture is heated to room temperature (25-30°C) for reaction to obtain styrylbissulfonylimide. Then, 4-(trifluoromethoxy)-benzenesulfonamide and lithium hydroxide in an equal molar ratio are placed in distilled water and stirred to a transparent solution. The distilled water is dried using a rotary evaporator to obtain a 4-(trifluoromethoxy)-benzenesulfonamide lithium salt monomer.
5. The method for preparing the polymer solid electrolyte film with alternating distribution of lithium salt and conductive chain segments obtained in claim 2, characterized in that: The synthesized electrolyte material was dissolved in dimethyl sulfoxide, heated and uniformly dispersed for 6-12 hours, and the uniform solution was poured into a PTFE petri dish and placed on a 70°C heating table for 24 hours to evaporate the solvent. The PTFE petri dish was then placed in an 80°C vacuum oven to completely evaporate the solvent, thereby obtaining the final electrolyte film.
6. The reaction in claim 2 is a "one-step quantitative grafting reaction", characterized in that The amount of amino group should be equal to the amount of anhydride group. The ratio of amino octaethylene glycol monomethyl ether (NH2-(CH2CH2O)-) to diamino oligomeric PEG (NH2-PEG-NH2, Mw=2000) is (1-4):
1.
7. The method for preparing the alternating copolymer lithium salt according to claim 3, characterized in that: The ratio of the mass of the thermal initiator to the total mass of the two monomers is 0.1 to 1% (ie, mass ratio), preferably 0.1 to 0.3%.
8. The method for preparing the alternating copolymer lithium salt according to claim 3, characterized in that: The polymerization time is at least 24 hours to allow the added monomers to be fully polymerized, preferably 30-48 hours.